Molecularly Imprinted Polymer-Based Electrochemical BioSensors for Haemophilus influenzae Rapid Detection - Naphatsawan Vongmanee; Jindapa Nampeng; Chuchart Pintavirooj; Sarinporn Visitsattapongse (Polymers, 2026)
.
Keywords: Biosensors and Analytical Detection; Electrochemical sensors and biosensors; Advanced biosensing and bioanalysis techniques